Looking at the Impacts of Transformational Leadership Skills and Organizational Climate on Job Satisfaction and Business Performance - Hikmat, Hikmat; Munandar, Dadang; Izzatusholekha, Izzatusholekha (Edukasi, 2023)
This research aims to determine the effect of transformational leadership skills and organizational climate on job satisfaction that affects the performance of the business at PT. Inti Jaya Purnama, Central Jakarta, DKI Jakarta. This research employed a quantitative research design with the survey method. The samples are 155 employees chosen using random sampling. Data are analyzed using the structural equation modeling based on Partial Least Squares (PLS-SEM) with the assistance of SmartPLS version 3.0. PLS is used in structural equation modeling based on a standardized coefficient of regression (β) that allows for the simultaneous examination of both the measurement and structural models. The research findings acquired via this approach are subsequently assessed 1) transformational leadership skills on job satisfaction with the value of t observation as much as 10.035 which is bigger than the tα as much as 1.975 with the value of significance as much as 0.000 which is less than 0.05; 2) Organizational climate affects positively and significantly on job satisfaction with the value of t observation as much 4.955 which is bigger than the tα as much as 1.975 with the value of significance as much as 0.000 which is less than 0.05; and 3) job satisfaction has a significant effect on business performance with the value of t observation as much as 22.687 which is bigger than the tα as much as 1.975 with the value of significance as much as 0.000 which is less than 0.05.